Hunting Success on Albany, Georgia Plantations: The Albany Quail Project's Modern Quail Management Strategy - H. Lee Stribling; D. Clay Sisson (National Quail Symposium Proceedings, 2017)
The Albany Quail Project began in March 1992 as a cooperative between Auburn University’s School of Forestry and Wildlife Sciences and the private quail plantation community surrounding Albany, Georgia. The goal of this collaboration was to increase population densities and hunting success of northern bobwhites (Colinus virginianus) on these properties. Issues important to the plantations were investigated via field research techniques (e.g. radio-telemetry) and then modifications in management regimes were put into practice. From 1992-2006 over 8,000 wild bobwhites were radio-tagged to study various demographic and population mechanism of bobwhites. The result has been a change in management style based on science creating the concept of Modern Quail Management (MQM) techniques. Bobwhite population densities and hunting success during the last decade on these properties have been higher and more stable than witnessed during any previous period in their history. On our primary study site during 1980-1996 the average number of coveys seen per hour was 3.9 (SE = 0.265) with a range of 2.7 - 6.5 (CV = 0.28). Following the implementation of MQM techniques this average during 1997-2005 increased to 7.7 (SE = 0.317) with a range of 6.9-9.7 (CV = 0.12) and population density has been maintained at or near 5 birds per ha. This manuscript provides a brief history of the Albany Quail Project, describes how results from these studies have contributed to the evolution of new management philosophies over the last decade, outlines what these changes have been, and describes how they have been successfully applied on numerous properties in the Albany area to improve bobwhite populations and hunting success.
Keywords: Colinus virginianus; Georgia; hunting; modern quail management; northern bobwhite; plantation; radio-telemetry